2004
DOI: 10.1007/s11178-005-0041-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropanation of betulin and its diacetate with dihalocarbenes

Abstract: Reactions of betulin, its diacetate, and 17-acetoxy-28-norlupan-3-one with dichlorocarbene generated from chloroform follow the [1 + 2]-cycloaddition pattern leading to the corresponding adducts in moderate to quantitative yield. In the reaction with betulin, [1 + 2]-cycloaddition is accompanied by dichlorocarbene attack on the primary hydroxy group to give the corresponding halogen derivative and formate. The addition of dichlorocarbene to betulin is strictly stereoselective, while the reaction with betulin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…12 The lupan triterpenoid betulin 8a on treatment with dichlorocarbene generated from CHCl 3 and NaOH under PTC conditions afforded the dichlorocyclopropane derivative 9a in 55% yield along with some side products (Scheme 3). 12 The lupan triterpenoid betulin 8a on treatment with dichlorocarbene generated from CHCl 3 and NaOH under PTC conditions afforded the dichlorocyclopropane derivative 9a in 55% yield along with some side products (Scheme 3).…”
Section: Phase Transfer Catalysis In the Synthesis Of Gem-dihalocyclomentioning
confidence: 99%
See 1 more Smart Citation
“…12 The lupan triterpenoid betulin 8a on treatment with dichlorocarbene generated from CHCl 3 and NaOH under PTC conditions afforded the dichlorocyclopropane derivative 9a in 55% yield along with some side products (Scheme 3). 12 The lupan triterpenoid betulin 8a on treatment with dichlorocarbene generated from CHCl 3 and NaOH under PTC conditions afforded the dichlorocyclopropane derivative 9a in 55% yield along with some side products (Scheme 3).…”
Section: Phase Transfer Catalysis In the Synthesis Of Gem-dihalocyclomentioning
confidence: 99%
“…The preparation of gem-dihalocyclopropane derivatives of some triterpenoids of lupan series under PTC was reported. 12 The lupan triterpenoid betulin 8a on treatment with dichlorocarbene generated from CHCl 3 and NaOH under PTC conditions afforded the dichlorocyclopropane derivative 9a in 55% yield along with some side products (Scheme 3). However, the diacetate of betulin 8b under similar reaction conditions afforded quantitative yield of the product 9b with high diastereoselectivity (95 : 5).…”
Section: Phase Transfer Catalysis In the Synthesis Of Gem-dihalocyclo...mentioning
confidence: 99%
“…( 1 H-1 H COSY and 13 C-1 H correlations) of the oxidative decarboxylation products and also of compounds described earlier [5][6][7][8][9][10], allowed us to make the unambiguous and full assignment of all carbon and hydrogen atom signals in these spectra and to reveal a criterion for the determination of the stereochemistry of the C-17 atom, which are complementary. One of the criteria is the value of the chemical shift of the C-13 signal.…”
mentioning
confidence: 97%
“…Previously, 5 it was shown that the addition of dichloro carbene to the C(20)-C(29) double bond of betulin diacetate affords two diastereomers (95 : 5 ratio); one of these was isolated in a pure state by recrystallization, while the second was obtained as a 1 : 1 mixture with the first one. In this study, compounds 2, 3, and 5 are formed as individual diastereomers.…”
mentioning
confidence: 99%